2018
DOI: 10.1051/0004-6361/201732085
|View full text |Cite
|
Sign up to set email alerts
|

Does the solar granulation change with the activity cycle?

Abstract: Context. Knowledge of the variation of the solar granulation properties (contrast and scale) with the 11-yr activity cycle is useful for a better understanding of the interaction between magnetic field and convection at global or local scales. A varying granulation may also contribute to irradiance variations and affect the p-mode damping rates and lifetimes. Aims. HINODE/SOT blue continuum images taken in the frame of the synoptic program at the disk center on a daily basis between November 2006 and February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…is dominated by the granulation variability, ν ∈ [ f , 2300] µHz, is not significantly affected by the solar magnetic cycle (see Seleznyov et al 2011;Muller et al 2018). Therefore, we can state that granulation variability is stationary with respect to the solar cycle (i.e., its statistical properties remain constant over the solar cycle).…”
Section: A Stationary Stochastic Colored Noisementioning
confidence: 94%
“…is dominated by the granulation variability, ν ∈ [ f , 2300] µHz, is not significantly affected by the solar magnetic cycle (see Seleznyov et al 2011;Muller et al 2018). Therefore, we can state that granulation variability is stationary with respect to the solar cycle (i.e., its statistical properties remain constant over the solar cycle).…”
Section: A Stationary Stochastic Colored Noisementioning
confidence: 94%
“…We report, for the first time, a direct measurement of granule variations in the quiet Sun along the cycle; indirect clues of global modifications in granulation (integrated over the whole Sun) had already been suggested by variations in Fraunhofer line bisectors (e.g., Livingston 1982;Livingston et al 1999). Moreover, previous works indicated that variations in granulation during the cycle could be only of weak amplitude (Muller et al 2018); here we were able to sufficiently lower our detection level thanks in particular to the high stability and quality of the SDO/HMI instrument.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, we can observe the evolution of the dynamical properties of the granulation over a solar cycle. Thanks to Hinode observations, variations in intensity contrast and in granulation scales have been shown to be smaller than 3% (Muller et al 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Attempts of investigating variations in the convection patterns over the activity cycle are not numerous (see, in particular, references in Roudier & Reardon 1998;Muller et al 2018). Lefebvre et al (2008) found that the granulation evolves with height in the photosphere but does not exhibit considerable variations in the activity cycle.…”
Section: Introductionmentioning
confidence: 99%